Protective Activity of Rhizobium leguminosarum bv. viciae Strain 33504-Mat209 against Alfalfa Mosaic Virus Infection in Faba Bean Plants - Ahmed Abdelkhalek; Shimaa Bashir; Hamada El-Gendi; Toufic Elbeaino; Wafaa M. Abd El-Rahim; Hassan Moawad (Plants, 2023)
The application of Rhizobium spp., nitrogen-fixing plant growth-promoting rhizobacteria, as biocontrol agents to enhance systemic disease resistance against plant viral infections is a promising approach towards achieving sustainable and eco-friendly agriculture. However, their potential as antivirals and biocontrol agents is less studied. Herein, the capability of Rhizobium leguminosarum bv. viciae strain 33504-Mat209 was evaluated to promote plant growth and enhance faba bean systemic resistance against alfalfa mosaic virus (AMV) infection. Under greenhouse conditions, the soil inoculation with 3504-Mat209 resulted in notable improvements in growth and an increase in chlorophyll content. This led to a marked decrease in the disease incidence, severity, and viral accumulation level by 48, 74, and 87%, respectively. The protective effect of 33504-Mat209 was linked to significant decreases in non-enzymatic oxidative stress indicators, specifically H2O2 and MDA. Additionally, there were significant increases in the activity of reactive oxygen species scavenging enzymes, such as peroxidase (POX) and polyphenol oxidase (PPO), compared to the virus treatment. The elevated transcript levels of polyphenolic pathway genes (C4H, HCT, C3H, and CHS) and pathogenesis-related protein-1 were also observed. Out of 18 detected compounds, HPLC analysis revealed that 33504-Mat209-treated plants increased the accumulation of several compounds, such as gallic acid, chlorogenic acid, catechin, pyrocatechol, daidzein, quercetin, and cinnamic acid. Therefore, the ability of 33504-Mat209 to promote plant growth and induce systemic resistance against AMV infection has implications for utilizing 33504-Mat209 as a fertilizer and biocontrol agent. This could potentially introduce a new strategy for safeguarding crops, promoting sustainability, and ensuring environmental safety in the agricultural sector. As far as we know, this is the first study of biological control of AMV mediated by Rhizobium spp. in faba bean plants.